Biosynthesis of the Dihydrochalcone Sweetener Trilobatin Requires Phloretin Glycosyltransferase2. Issue 2 (30th July 2020) - Wang, Yule; Yauk, Yar-Khing; Zhao, Qian; Hamiaux, Cyril; Xiao, Zhengcao; Gunaseelan, Kularajathevan; Zhang, Lei; Tomes, Sumathi; López-Girona, Elena; Cooney, Janine; Li, Houhua; Chagné, David; et al.
Abstract: Genetic, biochemical, and molecular characterization of phloretin glycosyltransferase2 reveals its importance to the production of sweet-tasting trilobatin (phloretin-4′-o -glucoside) in wild apple. Abstract: Epidemics of obesity and type 2 diabetes drive strong consumer interest in plant-based low-calorie sweeteners. Trilobatin is a sweetener found at high concentrations in the leaves of a range of crabapple ( Malus ) species, but not in domesticated apple ( Malus × domestica ) leaves, which contain trilobatin's bitter positional isomer phloridzin. Variation in trilobatin content was mapped to the Trilobatin locus on LG 7 in a segregating population developed from a cross between domesticated apples and crabapples. Phloretin glycosyltransferase2 ( PGT2 ) was identified by activity-directed protein purification and differential gene expression analysis in samples high in trilobatin but low in phloridzin. Markers developed for PGT2 cosegregated strictly with the Trilobatin locus. Biochemical analysis showed PGT2 efficiently catalyzed 4′-o -glycosylation of phloretin to trilobatin as well as 3-hydroxyphloretin to sieboldin. Transient expression of double bond reductase, chalcone synthase, and PGT2 genes reconstituted the apple pathway for trilobatin production in Nicotiana benthamiana . Transgenic M. × domestica plants overexpressing PGT2 produced high concentrations of trilobatin in young leaves. Transgenic plants were phenotypically normal, and no differences in disease susceptibility were observed compared to wild-type plants grown under simulated field conditions. Sensory analysis indicated that apple leaf teas from PGT2 transgenics were readily discriminated from control leaf teas and were perceived as significantly sweeter. Identification of PGT2 allows marker-aided selection to be developed to breed apples containing trilobatin, and for high amounts of this natural low-calorie sweetener to be produced via biopharming and metabolic engineering in yeast.